Flight scheduling problem, with time window, applied to a fractional jet ownership company - José Messias Magalhães Júnior (2013)
The present research addresses the problem of optimizing the flight schedule with time window applied to a fractional ownership jet company. The use of time window is intended to represent the situation in which the client is flexible to adjustment de departure time. This relaxation of time by the customer requesting air transport service enables the company to minimize the operational costs of the aircraft. In addition to the time window, the mathematical model includes the option to shared flight, in which the customers agree to make stops before reaching their final destination. In this work, different scenarios were analyzed, varying the time window 0-45 minutes in problems involving 09 to 30 clients. For the analysis of these scenarios, a tool was developed in AIMMS environment, called IOS (Icoaraci Optimization System). This tool has proved to be extremely useful in the development of this work. It has a user-friendly interface and is integrated into MS-EXCEL, where customer data are loaded. The Cplex12.4 is the solver responsible to reach the optimal flight schedule. For problems involving more than 10 clients, an heuristic was developed to provide a good and feasible solution. The use of time window and shared flight resulted in a reduction of up to 51.36% in total cost.